2022
DOI: 10.3389/fpubh.2022.872430
|View full text |Cite
|
Sign up to set email alerts
|

Can Neuropeptide S Be an Indicator for Assessing Anxiety in Psychiatric Disorders?

Abstract: Neuropeptide S (NPS) is a neuropeptide primarily produced within three brainstem regions including locus coeruleus, trigeminal nerve nucleus, and lateral parabrachial nucleus. NPS is involved in the central regulation of stress, fear, and cognitive integration. NPS is a mediator of behavior, seeking food, and the proliferation of new adipocytes in the setting of obesity. So far, current research of NPS is only limited to animal models; data regarding its functions in humans is still scarce. Animal studies show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 78 publications
0
3
0
Order By: Relevance
“…Our study exposed the diagnostic, prognostic, and therapeutic potential of NPS screening in patients with schizophrenia, especially in relation to the E/H domain. Generally, E/H symptoms reduction can be associated with the core impact of rehabilitation, which is anxiety reduction, which is related to the overall research on NPS [ 6 , 45 , 46 ]. The results were so specific and selective, repeated across various PANSS models, that NPS may be understood as the marker of excitement/Hostility symptomatology.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our study exposed the diagnostic, prognostic, and therapeutic potential of NPS screening in patients with schizophrenia, especially in relation to the E/H domain. Generally, E/H symptoms reduction can be associated with the core impact of rehabilitation, which is anxiety reduction, which is related to the overall research on NPS [ 6 , 45 , 46 ]. The results were so specific and selective, repeated across various PANSS models, that NPS may be understood as the marker of excitement/Hostility symptomatology.…”
Section: Discussionmentioning
confidence: 99%
“…The effect of neuropeptides is slow, but also much stronger, resulting in an apparent change in the modulation of the regulatory mechanism of metabolic pathways and gene expression. Markiewicz et al described the pharmacokinetic mechanism in detail in a previous publication [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Neuropeptide S (NPS) has multiple neuropsychiatric functions [7], and it has been postulated that it may play an important role in regulating cognitive functioning [8]. The problem is that so far, the studies have been conducted almost exclusively on animals [9].…”
Section: Introductionmentioning
confidence: 99%
“…There are only preliminary data on the relationship between the NPS/NPSR1 system and the course of schizophrenia [7]. A case-control comparison revealed that the low func-tioning NPSR1 Asn107 variant was significantly associated with schizophrenia [27].…”
Section: Introductionmentioning
confidence: 99%